2005
DOI: 10.1002/bdrc.20052
|View full text |Cite
|
Sign up to set email alerts
|

Teratogen-induced apoptotic cell death: Does the apoptotic machinery act as a protector of embryos exposed to teratogens?

Abstract: Considerable evidence has been collected demonstrating that many teratogens induce apoptotic cell death in embryonic structures that turn out to be malformed in fetuses and newborns. Apoptosis is a genetically regulated process that is realized by the activation of death and pro-survival signaling cascades, and the interplay between these cascades determines whether the cell exposed to apoptotic stimuli dies or survives. Therefore, there is intense interest in understanding how the apoptotic machinery function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 86 publications
1
16
0
Order By: Relevance
“…If this is the case, a model may be proposed in which the activation of some proapoptotic miRNAs may represent an adaptive response to teratogenic apoptotic stimuli, whereas other proapoptotic miRNAs are activated and/or antiapoptotic miRNAs are suppressed to strengthen teratogen-induced apoptosis. This model does not contradict results obtained from teratological studies implying that proapoptotic signaling may be indispensable for embryo protection again teratogenic stress [11]. It is also in agreement with the suggestion that miRNAs are ideal candidates for the safeguarding of organisms during environmental stresses [48,49].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…If this is the case, a model may be proposed in which the activation of some proapoptotic miRNAs may represent an adaptive response to teratogenic apoptotic stimuli, whereas other proapoptotic miRNAs are activated and/or antiapoptotic miRNAs are suppressed to strengthen teratogen-induced apoptosis. This model does not contradict results obtained from teratological studies implying that proapoptotic signaling may be indispensable for embryo protection again teratogenic stress [11]. It is also in agreement with the suggestion that miRNAs are ideal candidates for the safeguarding of organisms during environmental stresses [48,49].…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, apoptosis and cell proliferations are critically important processes of normal embryogenesis [9]. Teratological studies have revealed that the appearance of teratogen-induced structural anomalies is often preceded by excessive apoptosis in embryonic structures that are destined to be malformed [10,11]. At the same time, teratogen-induced apoptosis is also often registered in embryonic structures that appear normal at birth [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies also provided evidence that both p53-mediated apoptosis and p53-mediated cell arrest may be important steps in the pathogenesis of teratogen-induced anomalies. Importantly, however, as in the above studies, the presence of p53 was found to be associated with both the increased and the decreased teratological susceptibility of embryos, they led to the conclusion that p53 is able to act both as a 'teratological suppressor' and as a 'teratological initiator' (Torchinsky et al 2005).…”
Section: Introductionmentioning
confidence: 84%
“…The initiator caspase 9 operates in the mitochondrial pathway, whereas the initiator caspase 8 acts in the death-receptor pathway, while both pathways share the effector caspase 3 (Pommier et al 2004). Teratological studies revealed that at least one of these caspases is activated in embryos exposed to such teratogens as cyclophosphamide (CP), heat shock, sodium arsenite, diabetes, retinoic acid, methyltriazene (an alkylating agent), and ionizing radiation (Torchinsky et al 2005). The possibility that p53-mediated apoptosis may be associated with the activation of any of the above-mentioned caspases is suggested by the evidence demonstrating the ability of p53 to activate both the extrinsic and the intrinsic apoptotic pathways (Fridman & Lowe 2003, Pommier et al 2004, Michalak et al 2005).…”
Section: Introductionmentioning
confidence: 99%